2021
DOI: 10.3389/fgene.2021.706823
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: A Boy From a Consanguineous Family Diagnosed With Congenital Muscular Dystrophy Caused by Integrin Alpha 7 (ITGA7) Mutation

Abstract: Introduction: Congenital muscular dystrophy (CMD) is a group of early-onset disorders with clinical and genetic heterogeneity. Patients always present with muscle weakness typically from birth to early infancy, delay or arrest of gross motor development, and joint and/or spinal rigidity. There are various genes related to the development of CMD. Among them, mutations in integrin alpha 7 (ITGA7) is a rare subtype. The identification of disease-causing genes facilitates the diagnosis and treatment of CMD.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…These had various symptoms and different grades of severity. The consistent clinical features were muscle weakness and increased CK level [13].…”
Section: Defective Structural Proteins Of Basal Membrane or Extracell...mentioning
confidence: 81%
See 2 more Smart Citations
“…These had various symptoms and different grades of severity. The consistent clinical features were muscle weakness and increased CK level [13].…”
Section: Defective Structural Proteins Of Basal Membrane or Extracell...mentioning
confidence: 81%
“…Integrin α-7 deficient CMD: This CMD is caused by mutation in integrin α7 (ITGA7) and it is a rare subtype. This gene has 28 exons, among which 26 code for protein [13]. Only a few patients diagnosed with CMD were found to have ITGA7 mutation [6,[13][14][15][16] and it is not clear whether all variants are pathogenic mutations.…”
Section: Defective Structural Proteins Of Basal Membrane or Extracell...mentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiac function was reportedly normal. 254 Point Mutations c.1506-2A>G Congenital muscular dystrophy with severe neurocognitive difficulties 145 DCM dilated cardiomyopathy, LGMD Limb-Girdle muscular dystrophy, WWS Walker-Warburg syndrome, XLCM X-Linked cardiomyopathy. …”
Section: Introductionmentioning
confidence: 99%
“…Some studies have described skeletal muscle pathology or dysfunction in patients and mice lacking integrin α7, but these only involved a limited number of patients with ITGA7 deficiency with pediatric clinical presentations. 26 , 27 , 28 , 29 , 30 , 31 Only 1 study has reported a proband carrying variants in ITGA7 and MYH7 (myosin heavy chain beta) genes with features of cardiomyopathy. 29 Other family members demonstrating isolated cardiomyopathy only carried the MYH7 variant, and therefore the role of integrin α7 in cardiac function remains unknown.…”
mentioning
confidence: 99%